Pengaruh Media Sosial Tik Tok terhadap Interaksi Sosial Siswa Kelas Rendah Madrasah Ibtidaiyah (MI) - Almahdi, Achmad Arif; Suwardi, Suwardi; Nugroho, Imam Wahyu (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This study aims to determine the effect of Tik Tok social media on the social interaction of low grade students of madrasah ibtidaiyah (MI). The type of research used is quantitative with a survey method. The data collection technique uses questionnaires and documentation. The results of the study show that Tik Tok social media has an effect on the social interaction of low-grade students of Madrasah Ibtidaiyah (MI). The significance value between the Tik Tok social media variable (X) and the social interaction variable (Y) is 0.002. This value is less than 0.05 (0.002 <0.05). This means that simultaneously it can be concluded that the Tik Tok social media variable (X) has a significant effect on the social interaction variable (Y). The coefficient value between variable X and variable Y is 0.247. This value indicates the magnitude of the influence of Tik Tok's social media on social interaction is 24.7% and 75.3% is influenced by other factors. The regression coefficient X of 0.530 states that for every 1% addition of Tik Tok's social media value, the value of social interaction increases by 0.530. The conclusion that can be drawn is that Ha can be accepted and H0 is rejected.